Peripheral blood CD34+ cells efficiently engraft human cytokine knock-in mice - Saito, Yasuyuki; Ellegast, Jana M.; Rafiei, Anahita; Song, Yuanbin; Kull, Daniel; Heikenwalder, Mathias; Rongvaux, Anthony; Halene, Stephanie; Flavell, Richard A.; Manz, Markus G. (Blood, 2016)
Human CD34+ hematopoietic stem and progenitor cells (HSPCs) can reconstitute a human hemato-lymphoid system when transplanted into immunocompromised mice. Although fetal liver-derived and cord blood–derived CD34+ cells lead to high engraftment levels, engraftment of mobilized, adult donor-derived CD34+ cells has remained poor. We generated so-called MSTRG and MISTRG humanized mice on a Rag2−/−Il2rg−/− background carrying a transgene for human signal regulatory protein α (SIRPα) and human homologs of the cytokine macrophage colony-stimulating factor, thrombopoietin, with or without interleukin-3 and granulocyte-macrophage colony-stimulating factor under murine promoters. Here we transplanted mobilized peripheral blood (PB) CD34+ cells in sublethally irradiated newborn and adult recipients. Human hematopoietic engraftment levels were significantly higher in bone marrow (BM), spleen, and PB in newborn transplanted MSTRG/MISTRG as compared with nonobese diabetic/severe combined immunodeficient Il2rg−/− or human SIRPα-transgenic Rag2−/−Il2rg−/− recipients. Furthermore, newborn transplanted MSTRG/MISTRG mice supported higher engraftment levels of human phenotypically defined HSPCs in BM, T cells in the thymus, and myeloid cells in nonhematopoietic organs such as liver, lung, colon, and skin, approximating the levels in the human system. Similar results were obtained in adult recipient mice. Thus, human cytokine knock-in mice might open new avenues for personalized studies of human pathophysiology of the hematopoietic and immune system in vivo. •Human cytokine knock-in mice are improved in vivo models for multilineage engraftment of mobilized PB CD34+ cells.•Humanized mouse models might open new avenues for personalized studies of human pathophysiology of the hematopoietic and immune system.